Analisis Antibakteri Teh Kombucha Terhadap Bakteri Staphylococcus aureus Isolat Pus Ulkus Diabetikum - Rosyiid Amrijuldin; Tilawaty Aprina; Khoirul Rista Abidin; Khairul Bariyah (Indonesian Journal of Herbal and Biomedical Research, 2026)
Background: Diabetic ulcers are a chronic complication of diabetes mellitus that are frequently infected by Staphylococcus aureus. The increasing prevalence of antibiotic resistance has encouraged the search for natural antibacterial alternatives, one of which is green tea kombucha, which contains bioactive compounds produced during the fermentation process. Methods: This experimental study employed the disk diffusion method on Mueller–Hinton Agar (MHA). The samples consisted of green tea kombucha fermented for 7 days at concentrations of 20%, 30%, 40%, and 50%. Nebacetin was used as the positive control, while sterile distilled water served as the negative control. Bacterial isolates were identified using Mannitol Salt Agar (MSA). Statistical analysis was performed using the Mann–Whitney test to determine significant differences among the treatment groups. Results: Diabetic ulcer pus isolates exhibited the characteristic features of S. aureus, as indicated by the yellow color change of the culture medium. The antibacterial activity assay demonstrated that all kombucha concentrations inhibited the growth of S. aureus, with the largest inhibition zone observed at the 50% concentration (5.58 mm) and the smallest at the 40% concentration (4.30 mm). The Mann–Whitney test revealed a significant difference between the kombucha treatment groups and the negative control (p < 0.05). Conclusion: Green tea kombucha fermented for 7 days exhibited antibacterial activity against Staphylococcus aureus isolated from diabetic ulcer pus and shows potential as a natural antibacterial agent to support the treatment of wound infections in patients with diabetes.